Impoliteness Strategies in Facebook Comments on Religious-driven Sermons against the LGBTQ+ Community: A Pragmatic Analysis - Trisana Jyn Q Tomas; Mark Aaron Agbon Dacalanio; Mary Rose D Rival; Rechel B Lapaz; Mecca S Seguran (J-Lalite: Journal of English Studies, 2025)
This research aims to identify common impoliteness strategies employed by Facebook users in their comments on religious-driven sermons against the LGBTQ+ community. The researchers gathered 50 impolite comments and analyzed based on the Impoliteness theory by Jonathan Culpeper (1996). The data were gathered from Facebook comments and underwent descriptive qualitative analysis wherein each comment is given a description and analyzed as to how they are being used and interpreted. In terms of impoliteness triggers, it involved the following: insults, pointed criticism, unpalatable questions, dismissals, silencers, threats, context-driven impoliteness, and convention-driven impoliteness. Meanwhile, in terms of the impoliteness strategies used, it involved the following: bald-on record impoliteness, negative impoliteness, positive impoliteness, and sarcasm or mock impoliteness while withhold impoliteness. The analysis revealed that impoliteness strategies or utterances in the religious context are the terms that are used to destroy the image, criticize, and express strong disagreement with the addressee. The findings suggest that Facebook users have to be aware of their words to foster respect in online contexts.